Principals’ Administrative Strategies for School Effectiveness in Public Secondary Schools in Anambra State - Nnamdi Obikeze; Nebolisa Chinwe Mikella; Nnamdi Obikeze; Nebolisa Chinwe Mikella (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
This study examined principals' administrative strategies for school effectiveness in public secondary schools in Anambra State. Descriptive survey research design was adopted in carrying out the study. Three research questions and three hypotheses guided the study. The population of the study consisted all 263 principals in public secondary schools in Anambra State, the same was used as sample size. The instrument for data collection was structured questionnaires titled: Principals' Administrative Strategies Questionnaire (PASQ) and School Effectiveness Questionnaire (SEQ) which was formulated by the researchers to elicit responses from the respondents. The instrument was validated by three lecturers, while the reliability was ascertained using the Cronbach Alpha reliability method which yielded a coefficient of 0.88. The instrument used was a 38-item questionnaire to elicit responses from the respondents. Two hundred and sixty-three copies (263) of the questionnaire were administered to the respondents out of which 243 copies were completely filled and retrieved. Data collected were analyzed using mean and standard deviation to answer the research questions. The t-test statistics was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed that principals’ instructional supervision provides teachers with adequate information to become familiar with instructional delivery, enabling them to perform better on the job. This, in turn, increases school effectiveness and helps the school achieve its goals and objectives. Furthermore, the study revealed that principals who encourage input from teachers and involve them in the decision-making process adopt an administrative strategy that enhances school effectiveness. Additionally, it was found that a strong influence exists between principals' instructional supervision, leadership style, communication strategy, and school effectiveness, among other factors.